The belt and Road project and its impact in Middle East (Latakia University Journal - Economic and Legal Sciences Series, 2023)
China seeks to rapidly expand its political and economic influence through many tools. The most importance of which is the belt and Road project, which constitutes a unique strategic, economic, political, security, geographical vision. From a different perspective based on mutual respect and common interests. Without interfering the political of state or pressures, this is what distinguished the project and enjoys the support of the Arab Mediterranean countries and BRICS countries at the same time. However the Belt and Road has multiple repercussions, manifested in various geo-economic, and geo-political forms. Accordingly the study concluded that there is a multiple importance of the countries of Middle East in relation to China and the Belt and Road project.